Laser spectroscopy. Vol. 1, basic principles. (4th ed.) - Demtröder, W. (Springer, 2017)
Keeping abreast of the latest techniques and applications, this new edition of the standard reference and graduate text on laser spectroscopy has been completely revised and expanded. While the general concept is unchanged, the new edition features a broad array of new material, e.g., frequency doubling in external cavities, reliable cw-parametric oscillators, tunable narrow-band UV sources, more sensitive detection techniques, tunable femtosecond and sub-femtosecond lasers (X-ray region and the attosecond range), control of atomic and molecular excitations, frequency combs able to synchronize independent femtosecond lasers, coherent matter waves, and still more applications in chemical analysis, medical diagnostics, and engineering.